1954
DOI: 10.1002/lipi.19540561205
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bildung freier Radikale aus phenolischen Antioxydantien

Abstract: fur die IJmwandlung zur Seepodrei4. ilhnlich wie bei stark mit Cuund Hg-vergifteten Anstrichen (Schiffsbodenfarbe IIIAS) werden die Cpprislarven schon kurz nach der endgiiltigen Anheftung, aber noch vor Vollendung der Metamorphose abgetctet, sie werden dann sehr schnell von Bakterien und Protozoen verarbeitet und dann vom Wasser fortgespult.In Liisung wirkte DDT, wie zahlreiche Versuche zeigten, iin allgemeinen nicht todlich auf die Cyprislarven von Balarms improwisus. Hieraus ist zu schlieaen, da5 die Abtotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1955
1955
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It was at first suggested that the hydroxybenzyl radicals were produced in the initial step, i.e., reaction 13 (33,72,154,238), but it has since been shown that these radicals are secondary products arising from isomerization of the initially formed phenoxy radicals (74). There is now, in fact, abundant evidence from electron paramagnetic resonance measure- ments that the phenoxy radical is the initial oxidation product of alkylphenols (7,22,29,113,242). These radicals may be quite stable or may undergo rapid secondary reactions.…”
Section: F Chain-breaking Inhibitionmentioning
confidence: 99%
“…It was at first suggested that the hydroxybenzyl radicals were produced in the initial step, i.e., reaction 13 (33,72,154,238), but it has since been shown that these radicals are secondary products arising from isomerization of the initially formed phenoxy radicals (74). There is now, in fact, abundant evidence from electron paramagnetic resonance measure- ments that the phenoxy radical is the initial oxidation product of alkylphenols (7,22,29,113,242). These radicals may be quite stable or may undergo rapid secondary reactions.…”
Section: F Chain-breaking Inhibitionmentioning
confidence: 99%
“…(b) The dispositions of the t-butyl substituents at C-5 are all similar with one methyl group in-plane and directed toward H(4). The intra-ring angles at C (3,5) are diminished well below the trigonal norm in all cases, and also at C(2), with compensatingly large angles observed at C (4,6). (c) Considerable differences are observed in the geometry about CO (7) in respect of compounds (9) and (14); cJ: (18), presumably a consequence of involvement in the latter in hydrogen-bonding (see below).…”
Section: -(3'4'-dioxo-5'-tbutyltetruhydrofuran-2'-ylidene)-5-methoxy-...mentioning
confidence: 87%
“…Typical oneelectron oxidants convert it into the blue quinone (1) which has been shown to be in equilibrium with the arene oxide (2) and the oxepino [2,3-b]benzofuran (3).1,2 In inhibiting autoxidation, BHA must itself be oxidized and in fact the blue colour of the quinone (1) has been observed in lard stabilized with BHA. 3 Since there are indications that singlet oxygen may be involved in biological ~x i d a t i o n , ~ it appeared of interest to examine the reaction of the oxepine (3), the major component of the equilibrium mixture, with this reagent. The reaction of the equilibrium mixture oxepine-benzene oxide itself with singlet oxygen has been reported5 to yield the endoperoxide (4) which readily isomerizes to trans-benzene trioxide (5).…”
mentioning
confidence: 99%